Négy ablak – a Debreceni Egyetem és a reformáció: (Ünnepi megemlékezés – 2017. szeptember 27.) - Szerkesztőség, A (Gerundium, 2018)
Four Windows – University of Debrecen and the Reformation (Celebratory Commemoration – 27 September 2017) The University – founded in Debrecen in 1912 – has always emphasised its roots attached to the Reformed College. The aim of the festive council held on 27 September 2017 was to recall the several centuries-old close connection between the Reformation and the traditions of the University and the city through the college’s foreign relationships. The crystal windows installed in the University Aula in 1938 picture the Reformed College and its historical relations, the important stations of the Debrecen students’ travels to foreign universities, namely Zurich, Utrecht, Wittenberg and Geneva. They also perpetuate the latin names of the four traditional university faculties: Jurisprudentia, Philosophia, Medicina, Theologia. In the commemoration high-ranking representatives of the three partner countries – that became important to the city of Debrecen, the University of Debrecen and the Reformed College based on the Reformation – commemorated about the more centuries-old protestant relationships between Debrecen and Germany, The Netherlands and Switzerland. In the following, we publish two welcome speeches and two lectures heard in the celebratory commemoration.